PENGARUH KONSENTRASI BAKTERI FOTOSINTETIK YANG DIAPLIKASIKAN PADA FASE INISIASI BUNGA TERHADAP PRODUKSI BENIH KACANG MERAH INERIE - Yosefina Lewar; Ali Hasan; Stormy Vertygo; Maria Klara Salli (Politeknik Negeri Lampung., 2026)
Photosynthetic bacteria are used as autotrophic bacteria capable of carrying out photosynthesis independently. They also serve as atmospheric nitrogen-fixing microorganisms that contribute to the nitrogen supply for plants and enable more efficient utilization of inorganic nitrogen fertilizers, thereby enhancing nutrient uptake by plants. The effectiveness of photosynthetic bacteria is also influenced by their concentration. An appropriate concentration of photosynthetic bacteria affects plant growth and yield. The objective of this study was to determine the optimal concentration of photosynthetic bacteria to improve nutrient availability and uptake in order to increase the seed yield of Inerie kidney bean variety grown in lowland areas. The study was designed using a Randomized Block Design with treatments consisting of different concentrations of photosynthetic bacteria (K), namely K1 (10 mL L⁻¹), K2 (15 mL L⁻¹), K3 (20 mL L⁻¹), K4 (25 mL L⁻¹), K5 (30 mL L⁻¹), and K6 (35 mL L⁻¹). The results showed that the concentration of 15 mL L⁻¹ was the most effective, producing 125.19 seeds per plant, a seed weight of 40.89 g per plant, and a total seed weight of 642.54 g per 3 m² plot. Keywords: Photosynthetic Bacteria, Inerie, Concentration, Inerie, Kidney Bean